Effect of Respiratory Inhibitors on the Motility of Pseudomonas fluorescens - Faust, M. A. (1969)
The translational motility of Pseudomonas fluorescens was weakly inhibited by oligomycin, Dicumarol, 2,4-dinitrophenol, 2n-heptyl-4-hydroxyquinoline N-oxide, and potassium cyanide. Atabrine and antimycin A together with potassium cyanide immediately immobilized this bacterium, but antimycin A alone was without effect. Gramicidin D also immobilized P. fluorescens, but its action was inhibited by K(+) and NH(4)(+) ions. In like manner, the effect of p-chloromercuribenzoate could be counteracted with cysteine, thereby suggesting the involvement of —SH groups in flagellar motility processes. It appears that the energy required for motility of P. fluorescens is generated by oxidative phosphorylation mediated by the cytochrome system.